Rescue Fibrinolysis in STEMI Patients with Failed Primary Percutaneous Coronary Intervention at Hanoi Medical University Hospital - Bui Hai Hoang; Dinh Hung Vu; Michael M. Dinh; Nguyen Dai Nghia Phan; Thi Huong Thao Bui; Giang Phuc Do; Lan Hieu Nguyen (Emergency Care and Medicine, 2025)
Background: ST-elevation myocardial infarction (STEMI) is a life-threatening emergency. Primary percutaneous coronary intervention (PPCI) is the preferred reperfusion strategy, provided it is performed promptly (within 120 min of the ECG-based diagnosis). However, the failure rate of PPCI remains high, particularly in patients with more severe conditions, potentially leading to serious complications. Objective: Through this case, we want to introduce coronary fibrinolysis as a rescue therapy after failing with primary PPCI. Methods: Case report. Results: We reported a clinical case of a STEMI patient who underwent coronary fibrinolysis as a rescue therapy after PPCI failure. The patient was a 62-year-old male patient who was a 40-pack-year smoker. He was diagnosed with STEMI and immediately received PPCI, but the aspiration process and angioplasty were unsuccessful. Subsequently, we decided to use coronary fibrinolysis and the follow-up coronary angiography showed coronary revascularization, and chest pain was resolved. Conclusions: This case highlighted a potential therapeutic approach of coronary fibrinolysis for patients experiencing PPCI failure.